2019
DOI: 10.1097/mpg.0000000000002365
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use in Adolescents and Young Adults With Inflammatory Bowel Diseases

Abstract: Objectives: Adolescents and young adults (AYAs) with chronic illnesses use substances at similar, if not greater, rates compared to healthy peers. The present study aimed to examine rates and patterns of tobacco use, marijuana use, and binge drinking in AYAs with inflammatory bowel diseases. We expected that substance use would be associated with poorer physical health, psychosocial functioning, and disease management. Methods: One hundred thirty-two AY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…Of note, this association persisted on bivariate and multivariate analyses even when the presence of tobacco use was excluded (data not shown). Although a previous report found an association between PSU and disease activity, 19 we found no such association in this study. Our analysis utilized endoscopically confirmed disease activity, rather than subjective, symptomatic‐based estimates of disease activity, which might have contributed to this variation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Of note, this association persisted on bivariate and multivariate analyses even when the presence of tobacco use was excluded (data not shown). Although a previous report found an association between PSU and disease activity, 19 we found no such association in this study. Our analysis utilized endoscopically confirmed disease activity, rather than subjective, symptomatic‐based estimates of disease activity, which might have contributed to this variation.…”
Section: Discussioncontrasting
confidence: 99%
“…Several findings from this investigation were similar to those of previous studies. For example, we reported an incidence of PSU similar to that previously described in adolescents and young adults with IBD (20.6% vs 18.2%) 19 . This was also similar to a previous estimate of substance use disorder (16.6%) in adults with IBD 20 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Increased risk for SUDs was demonstrated in studies in paediatric and young adults with IBD [ 95 ]. It is worth noting that in another study in adolescents and young adults with IBD majority of them (76/132) were abstainers; however, those reporting usages of marihuana and binge drinking episodes have been also smoking cigarettes [ 96 ]. Furthermore, two large studies from Sweden on early onset IBD and adult-onset IBD shown a higher prevalence of substance misuse compared to both population and sibling controls [ 41 , 97 ].…”
Section: Alcoholmentioning
confidence: 99%